Pendayagunaan Wakaf di Tengah Pandemi Covid-19 Dalam Perspektif Maqashid Al-Syariah - M. Miftakhuddin; Khofifah Trisnah Lestari; Aniroh Aniroh; Hendri Hermawan Adinugraha (LPPM ISNJ Bengkalis, 2021)
The use of waqf instruments to overcome social and economic problems should also provide opportunities for handling the Covid-19 pandemic that is currently hitting the world. Handling a pandemic requires clear and strategic objectives, as stated in the maqashid sharia concept. This paper aims to analyze the use of waqf in the midst of the Covid-19 pandemic and its suitability with the perspective of maqashid sharia. The method used in this research is a qualitative method with an analysis-descriptive approach from a literature study. The results showed that in Indonesia, the use of waqf to overcome the problem of the Covid-19 pandemic is still not optimal, but waqf has great potential in providing hospitals and other health facilities. In the perspective of maqashid sharia, the utilization of waqf is also in accordance with the description of three concepts of needs according to As-Syatibi, namely dharuriyah, hajiyah, and tahsiniyah.